Engineering active sites on nitrogen-doped carbon nanotubes/cobaltosic oxide heterostructure embedded in biotemplate for high-performance supercapacitors. (September 2022) - Li, Kailin; Teng, Hao; Sun, Qing; Li, Yongfei; Wu, Xiaoxue; Dai, Xingjian; Wang, Yi; Wang, Simeng; Zhang, Yifan; Yao, Kexin; Bao, Zhihao; Rao, Jinsong; et al.
Abstract: At present, both easy agglomeration of carbon nanotubes themselves and waste caused by chemical vapor deposition (CVD) have great pollution, which limits the use of carbon nanotubes (CNTs). A large number of hollow polyhedrons containing N-doped carbon nanotubes and Co3 O4 nanoparticles (Co3 O4 NPs) were well fabricated on a biotemplate by hydrothermal method, stirring method and pyrolysis process. The regular polyhedron was uniformly arranged on the external surface of diatomite with a natural porous structure, which aims to avoid the agglomeration of CNTs. The electrochemical testing result shows that the composite has promising electrochemical performance, which is embodied in a high specific capacity 894.6 F/g at 2 A/g, good rate performance and high cycling property. Finally, an assembled Co3 O4 NP@CNTs@Diatomite//GR asymmetric supercapacitor has maximal energy density of 36.8 Wh/kg and maximal power density of 16, 326.6 W/kg. Indeed, electrode design in this work provides an environmental synthesis idea for the decoration of CNTs on a certain substrate and displays an original electrode material based on diatomite. Highlights: N-doped CNTs@Co3 O4 nanoparticles was successfully synthesized via hydrothermal method, stirring method and pyrolysis process; The synthesis method of CNTs in this work can solve the exhaust pollution problem resulted from traditional method (CVD); Nitrogen doped CNTs can boost the electron transfer efficiency and enhance the electrochemical performance of electrodes. Co3 O4 NP@CNTs@Diatomite electrode has an excellent electrochemical performance and the asymmetric supercapacitor has a high energy density;